Pipeline pigging and inspection technology - Tiratsoo, J. N. H. (Woburn, MA : Butterworth-Heinemann, 1999)
This reference focuses on oil, gas, and products pipeline, both on- and offshore. You'll understand why, when, and how to pig a line.
Keywords: Pipeline pigging; Pipelines -- Inspection; Pipelines -- Maintenance and repair; Electronic books